Spiritualia and pastoralia : exomologesis Ecclesiastes 1 - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974 ;, 2015)
The Collected Works of Erasmus presents these two important works, complete with extensive introductions and annotations, in an elegant and precise modern translation for the first time.